(untitled) (Abhat Journal, 2023)
The study of soil is of great importance because of its direct impact on agricultural production. Therefore, this research, dealt with the types of soils in Al-Batnan region, their classification, their geographical distribution, the diversity of vegetation according to the type of soil, and the availability of the necessary elements that the plant obtains from the soil, such as iron, calcium, nitrogen, magnesium, and others. The research reviewed some of the studies conducted in the past, whether at the level of individuals or international companies and institutions that conducted many studies in several types of soil to know the productive capacity and suitability for cultivation The study shows that there is a noticeable variation in the type of soil from one place to another, depending on the natural conditions such as the climate, the geological structure and the rock from which it is derived. , and also by torrents (water erosion).